ELECTRONICS WORD-OF-MOUTH, SOCIAL MEDIA INFLUENCERS, AND ATTITUDES TOWARD SOCIAL MEDIA INFLUENCERS INFLUENCING PURCHASING DECISION AND BRAND EQUITY ON THAI FACIAL SKINCARE OF GENERATION Y CONSUMERS IN BANGKOK - Naksri, Ananya; Sakulkijkarn, Wasan (Journal of KMITL Business school, 2023)
The objectives of this research to study the factors of electronics word of mouth (EWOM), social media influencers, and social media influencers’ source credibility influencing purchasing decision and brand equity of Thai facial skincare brands in Bangkok Metropolitan. The sample in this research included 400 generation Y people in Bangkok Metropolitan who have used Thai facial skincare. The respondents mostly are female private company employee who have bachelor’s degree, and earn around 30,001 – 45,000 baht per month. The results of hypothesis testing revealed that social media influencers’ source credibility and brand equity influence purchasing decision of Thai facial skincare brands. In addition, electronics word of mouth (EWOM), social media influencers, and social media influencers’ source credibility influence brand equity of Thai facial skincare brands.